P35 Are children who need help in contact with services?/what do we know about patterns of service contact?. (26th August 2022) - Mathews, Frances; Ford, Tamsin; Newlove-Delgado, Tamsin
Abstract : Background: Even prior to the Covid-19 pandemic, referrals to child and adolescent mental health services have been rising, in conjunction with increased focus and demand on school based mental health support. This study investigates whether children with mental health problems are becoming more or less likely to be in contact with sources of help, examining secular trends using NHS Digital's national child mental health surveys. These are the only repeated national epidemiological surveys to include standardised psychiatric diagnostic assessments in cross-sectional community samples of children and young people, using stratified probability sampling. Data Mental Health of Children and Young People (MHCYP) 2017 and British Child and Adolescent Mental Health Surveys 1999 and 2004 (BCAMHS), including ICD-10 psychiatric diagnoses from the validated Development and Wellbeing Assessment and parent and young person reported mental-health-related contact with a range of public sector services. Methods: Descriptive and trend analyses (using Stata v.17) of prevalence of service contact in relation to diagnosis amongst participants in 1999, 2004 and 2017, using survey weights to take account of selection probabilities and non response. Analysis is ongoing, early analyses of 2017 data are presented in this abstract. Results: In MHCYP 2017 (n=7, 654; 5 to 19 years; mean age 11.2; 49.7% female), of those with a diagnosis, a quarter (24.9%) reported contact with specialist mental health services, and 67.8% reported mental health-related contact with any education, health or social care service. In 5 to 16 year olds, males were more likely to have contact than females (75.1%, 95% CI 70.5–79.1% versus 64.3%, 95% CI 58.7–69.6%, p=0.0025). In 17 to 19 year olds, levels of service contact were higher amongst females (59.0%, 95% 48.8–68.4%) than males (47.8%, 95% CI 34.4–61.7%), although confidence intervals for estimates overlapped. Conclusion: Whilst most participants with a diagnosis reported some type of service contact, only a quarter had contact with a specialist service (similar to the proportion reported in BCAMHS 2004). There were also gender and age differences in patterns of contact. Analyses in progress are examining trends in contact as well as trends in inequalities in contact to identify groups who may be under-served. Given that Covid-19 is likely to have amplified existing inequalities, and has impacted child mental health at a population level, our analyses will incorporate data from MHCYP 2020 & 2021 once these become available.